Medical Ethics in the Age of Artificial Intelligence: A Review of High Table Forum - Liu, Haoyi; Liu, Shiyu (The Journal of Medicine, Humanity and Media, 2025)
On the afternoon of July 9, 2025, a high-table forum on "Medical Ethics in the Era of Artificial Intelligence" was successfully held, co-sponsored by the School of Journalism and Communication of Peking University and the journal Chinese Medical Ethics. As one of the sub-sessions of The 8th “Medicine, Humanity and Media”Health Communication International Conference & PhD Symposium, the forum brought together experts from various fields to share and discuss topics such as the ethical governance of AI-assisted diagnosis, the ethical self-reflexivity of medical artificial intelligence, ethical assessment, ethical review strategies and legal responses.